A PYRAMID WITH RAMP IN OLIVAR OF SAN ISIDRO - Casas Salazar, Lyda (2012)
The study is based on the analysis of a “field report” found in the official records of the National Institute of Culture, it yielded important information from an archaeological site -now gone- that was excavated for Luis Ccosi Salas, was more 60 years in the Summer of 1951. Was located in El Olivar de San Isidro, and his story now becomes, therefore, be a “pyramid with ramps. The author of the document in question provided descriptions of all rooms and architectural elements. Similarly, functions and values assigned to each set. In addition, illustrated the architectural details with care. This study examines the formal characteristics of the site, and integrates the architectural discovered in a certain time. Finally enter your question in the context of the central coast. This discusses the new theoretical account of the operation “ramped pyramids.”